Carbon Monoxide Modified Atmosphere Packaging Beef Shelf Life Studies - Rini Ariani Basyamfar (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
The combination of O2, CO2, and low concentrations of CO in CO-MAP has repeatedly been shown to increase the shelf-life of red meat products. Concentrations of CO2 of 30% has been shown to slow microbial growth while O2 preserves the natural color of red meat. The addition of low concentrations of CO (0.4%) preserves the color stability of the meat while allowing for lower levels of O2 which reduces the oxidative spoilage of the product. Shelf-life extension of 5 to 10 days above traditional MAP has been seen with CO-MAP technologies. The addition of active/smart films such as antimicrobial films and/or the combination of irradiation further extends the shelf-life of red meat. Undetectable levels of E. coli at storage temperatures as high as 10oC at 28 days have been shown with CO-MAP and irradiation.